Comparison of the diagnostic performance of abbreviated MRI and full diagnostic MRI using a computer-aided diagnosis (CAD) system in patients with a personal history of breast cancer: the effect of CAD-generated kinetic features on reader performance. Issue 10 (October 2019) - Ha, T.; Jung, Y.; Kim, J.Y.; Park, S.Y.; Kang, D.K.; Kim, T.H.
Abstract : AIM: To compare the diagnostic performance of abbreviated magnetic resonance imaging (MRI) and full diagnostic MRI with computer-aided diagnosis (CAD) system in patients with a personal history of breast cancer and to evaluate how the kinetic features affect the performance of two radiologists. MATERIALS AND METHODS: Between 1 January 2014 and 31 December 2017, 3, 834 breast MRI examinations in 2, 310 patients with a history of breast cancer comprised the study population. MRI images were reviewed retrospectively by two radiologists. First, two radiologists independently reviewed T1-weighted images scanned at 90 seconds after the contrast medium injection and T2-weighted images. After 6 months, the two readers reviewed contrast-enhanced T1-weighted images with five consecutive delayed images using CAD. The diagnostic performance of the abbreviated-sequence and full-sequence MRI were compared. RESULTS: Fifty-one intramammary recurrences were detected with breast MRI in 47 patients. Of the 51 tumour recurrences, 36 (70.6%) lesions occurred >3 years after initial cancer surgery and seven (13.7%) lesions at <2 years after initial surgery. The sensitivity and specificity were 92.2–94.1% and 97.6–98.6% on the abbreviated sequence and 94.1–96.1% and 97.9–98.3% on the full diagnostic MRI. Of 51 malignant lesions, six showed delayed persistent pattern, of which three lesions were non-mass enhancement and three lesions were small enhancing masses <1 cm. CONCLUSION: Overall diagnostic performances of abbreviated MRI and full diagnostic MRI were similar in both readers. The CAD-generated kinetic features could affect reader performance and the sensitivity could be improved or the specificity improved according to the reader. Highlights: Using a CAD system could cause false negative or false positive according to the readers and lesion types. The delayed persistent kinetic curve pattern could decrease the sensitivity especially in small cancers or cancers presented as non-mass enhancement. The diagnostic performance of full-dynamic sequence with CAD system was not significantly different with that of abbreviated sequence.